Dipeptidyl peptidase 4 inhibitors attenuate cardiac ischaemia–reperfusion injury in rats with diabetes mellitus type 2. (22nd December 2020) - Bradic, Jovana; Milosavljevic, Isidora; Bolevich, Stefani; Litvitskiy, Peter F; Jeremic, Nevena; Bolevich, Sergey; Zivkovic, Vladimir; Srejovic, Ivan; Jeremic, Jovana; Jovicic, Nemanja; Mitrovic, Slobodanka; Jakovljevic, Vladimir
Abstract: The aim of our study was to assess and compare the effects of dipeptidyl peptidase 4 (DPP4) inhibitors, saxagliptin and sitagliptin, on metabolic control of disease and cardiac function in rats with diabetes mellitus type 2 (T2DM). This research would provide novel understanding into the potentially protective effects of DPP4 inhibitors in helping salvage of the heart exposed to ischaemia–reperfusion (I–R) injury. Forty‐eight Wistar albino rats were randomly divided into four groups: CTRL, Control healthy group; T2DM, rats with T2DM; T2DM + Sit, rats with T2DM treated with 0.6 mg/kg of sitagliptin; T2DM + Sax, rats with T2DM treated with 0.45 mg/kg of saxagliptin for 3 weeks. At the end of the protocol, in vivo cardiac function was assessed by echocardiography, while in the blood samples glucose and insulin were determined. Additionally, ex vivo heart function was estimated on a model of I–R injury using Langendorff apparatus. Immunohistochemical analysis was used to determine the degree of myocardial apoptosis and necrosis, while DPP4 staining was performed to assess the cardiac DPP4 expression. Data were analyzed using a one‐way analysis of variance (ANOVA) and the post hoc Bonferroni test for multiple comparisons. Improved glycoregulation was noticed in rats that received DPP4 inhibitors compared to untreated diabetic rats ( P  < .05). Moreover, better in vivo systolic function was observed in rats treated with both DPP4 inhibitors as evidenced by an increase in fractional shortening when compared to T2DM ( P  < .05). Most parameters of cardiac function in treated rats remained unaltered during reperfusion, thus suggesting that both drugs protected myocardium during flow restoration. Better effects on coronary circulation were achieved after sitagliptin application. Additionally, both DPP4 inhibitors showed similar potential to attenuate cardiac necrosis and apoptosis. Saxagliptin and sitagliptin might be efficient in preserving myocardial function and morphology in ex vivo induced I‐R cardiac injury in rats with T2DM. Abstract : Chronic treatment with saxagliptin and sitagliptin improved glycoregulation and preserved the heart after ischemia‐reperfusion by decreasing apoptosis and necrosis.